2011
DOI: 10.1111/j.1600-0625.2011.01283.x
|View full text |Cite
|
Sign up to set email alerts
|

The cholinergic system in guttate psoriasis with special reference to mast cells

Abstract: Patients with guttate psoriasis have been reported to respond to anticholinergic treatment. We wanted to know how the cholinergic system could be involved in this process. Mast cells are characteristic components of the inflammatory infiltrate of guttate psoriasis. We therefore studied the cholinergic system in both epidermis and mast cells of 10 patients with guttate psoriasis in involved and uninvolved skin on protein level using immunofluorescence and in a mast cell line (HMC-1) using PCR. Both in vivo and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…Therefore, these results beg the question: What signalling mechanism is activated by the manifestation of colitis that could induce these mast cells in the distally located skin? Of central importance to this question are the high levels of nicotinic and muscarinic AChR expression on the mast cell surface and the ability of these ligand‐activated receptors to induce degranulation of the cell . Excessive degranulation invariably leads to cellular dysfunction, indicating that the non‐neuronal cholinergic system (via increased plasma acetylcholine levels) may play a role in the phenotype observed in our DSS‐treated mouse mode.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, these results beg the question: What signalling mechanism is activated by the manifestation of colitis that could induce these mast cells in the distally located skin? Of central importance to this question are the high levels of nicotinic and muscarinic AChR expression on the mast cell surface and the ability of these ligand‐activated receptors to induce degranulation of the cell . Excessive degranulation invariably leads to cellular dysfunction, indicating that the non‐neuronal cholinergic system (via increased plasma acetylcholine levels) may play a role in the phenotype observed in our DSS‐treated mouse mode.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, increased numbers of activated mast cells are often observed in and around lesional psoriatic skin, and increasing evidence suggests that mast cells are functionally important key immunocytes in the pathogenesis of psoriasis (Carvalho, Nilsson & Harvima, 2010; Namazi, 2005; Radosa et al, 2011; Suttle et al, 2012; Toruniowa & Jablonska, 1988). Recently, we have shown that CB1 activation limits excessive mast cell activity and even inhibits mast cell maturation of resident, intracutaneous progenitors (Sugawara et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…3A). Mast cells have AChRs, and degranulation of mast cells is regulated by these receptors111213. Destruction of the skin barrier on day seven may have involved the degranulation of mast cells via cholinergic signals.…”
Section: Discussionmentioning
confidence: 99%